(Study on Extraction of Blue Colouring Telang's (Cliteria ternatea L.) And Its Characteristics) - Tiurlan Farida Hutajulu; Aan Yulistia (Balai Besar Industri Agro, 2006)
This research is intended to study the type of extraction solvent and to characteristize the blue colour of telang's flowers as a food colouring material,using ethanol 10%,30%,50%,95%,atanol-acetic 1%,5%,10% and water for 24 hours,at room temperature.The characteristic of blue colour of telangs flower were analyzed with qualitative and quantitative analysis.The highest yield was 7.64%(by using)eatanol-acetic 10% solvent and the lowest yield was 4.75% by using water.The absorbance intensity of blue colouring with water solvent using chromameter were green and blue.Meanwhile for those by using etanol-asetat solvents were red and blue.The melting points of blue colouring was 54.1 degree C-55.0 degree C.It was obtained that in acidic solution (pH<4.5)the solution has red colour.In neutral solution (pH 7-8)the colour was blue and in basic solution (pH>9),it was greenish to colourless.The Rf points of blue colouring were 0.13;0.27;0.38;0.50 and 0.63 and those consist of delpyne 3,5 diglucose;delpydine-3glucose,malvidine-glucose and petunidine.The highest concentration of colour quantitative analysis was2320.39 ppm.The flavonoid and alkaloid result by using HPLC analysis was 6.56 ppm and 318.03 ppm.The analysis result of ca-oksalat and sulphur was 215.36 ppm